PENDEKATAN PASTORAL KONSELING PADA SUAMI ISTRI YANG BELUM BERCERAI TETAPI SUDAH PISAH RUMAH - Irene Avionita Petangpulu (HOSPITALITAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
couples who are legally married but living separately. The case study focuses on the psychological, spiritual, and social struggles faced by a wife after her husband suffered a severe accident, which led to behavioral changes and disruption of family functioning. Using a qualitative approach and case study method, the findings reveal that pastoral counseling contributes significantly to holistic recovery emotionally, spiritually, and relationally. Key counseling functions such as guidance, reconciliation, healing, and spiritual empowerment serve as essential tools in supporting the counselee. The article recommends strategies such as friendship-based counseling, continuous accompaniment, communication mediation, and collaboration with professionals as relevant and effective approaches in contextual pastoral counseling services.